Functional Biscuits with Soy Protein - Ekaterina S. Statsenko; Mikhail A. Shtarberg; Eugene A. Borodin (Техника и технология пищевых производств)
As a rule, modern confectionery products have added nutritional value, which makes them functional products. As a popular snack, biscuits are a promising object for fortification with functional ingredients. This article introduces a new formulation for biscuits fortified with soy protein. The research featured crushed soy protein obtained using a patented technology (patent No. 2218816). The experimental biscuits included a mix of wheat flour with 2.5–15.0% soy protein. The control sample was represented by commercial biscuits of the Arktika brand. Physicochemical and other quality indicators were determined by standard methods. The isoflavonoid test involved high performance liquid chromatography with methanol:water eluent. The experimental biscuits had a higher nutritional value; the absorption indicator fell from 196 to 172%. The crude gluten content dropped from 30.7 to 28.4%. The optimal content of soy protein in the new formulation was below 7.5% of the total mass of wheat flour. A higher mass fraction brought the absorption index below the standard value (˂ 170%) and spoiled the porosity and brittleness. Compared with the control sample, the nutritional value of the experimental sample improved as follows: protein – by 21.6%, fat – by 14.1%, minerals – by 11.1%, isoflavones – by 140.8% (from 4.83 to 11.63 mg/100 g). Total carbohydrates dropped by 6.5%. The formulation demonstrated good prospects for industrial production. The new biscuits with soy protein can be classified as functional food: compared to the conventional biscuits, the recommended daily intake (100 g) for phosphorus increased from 11.7 to 20.1%, vitamin E – from 12.6 to 18.0%, for isoflavones – from 9.6 to 23.2%.